The Contribution of Islamic Family Institutions to Eldercare Services in Brunei Darussalam - Muhammad Furqan Firdaus Bin Dr. Haji Samsul Muawan; Cecep Soleh Kurniawan (CV. ULIL ALBAB CORP, 2024)
Brunei Darussalam has an elderly population and is one of ASEAN's fastest-aging countries, yet there is no structured framework for eldercare based on Islamic principles. Regardless of existing goals and programs, the government has moved quickly to implement them. Islam emphasizes the importance of family institutions in caring for the elderly, and their involvement in this process must be emphasized on a regular basis. This study looks at (1) Western and Islamic perspectives on aging and age levels, (2) the challenges that senior citizens face, (3) the government's dynamic mechanism for addressing senior citizen welfare, and (4) the development of a comprehensive framework for the sustainability of eldercare in Brunei Darussalam. The study employs a qualitative technique, using library interviews, observation and document analysis, and data analysis using NVivo Version 14. The findings suggest that family institutions' responsibilities have a substantial influence on senior citizen care and lower the risk of aging in Brunei Darussalam. Overall, the role of family institutions in Brunei Darussalam is critical to the well-being of older individuals. Strengthening family relationships and assuring active engagement in eldercare can dramatically reduce the dangers associated with aging, resulting in healthier and more meaningful lives for elders.